Предмет: Алгебра,
автор: Luba2109
х^2-2х-3 разложите пожалуйста
Ответы
Автор ответа:
0
D=b^2-4ac=(-2)^2-4*1*(-3)= 16
x1= (-b+√D)/2a= -(-2)+4/2*1=3
x2=(-b-√D)/2a= -(-2)-4/2*1=-1
a ( x – x1 ) ( x – x2 ) = a ( x – 3) ( x + 1)
x1= (-b+√D)/2a= -(-2)+4/2*1=3
x2=(-b-√D)/2a= -(-2)-4/2*1=-1
a ( x – x1 ) ( x – x2 ) = a ( x – 3) ( x + 1)
Похожие вопросы
Предмет: Физика,
автор: goncharenkov356
Предмет: Биология,
автор: bessonalex7
Предмет: Алгебра,
автор: natalyasedova1975
Предмет: Литература,
автор: ilya12312313
Предмет: Математика,
автор: irina12345789